The Impact of Independent Learning on Academic Achievement in Social and Science Education Among Sixth Grade Elementary Students - Meilany, Nur Isdha; Kawuryan, Sekar Purbarini; Adi, Banu Setyo (Universitas Pendidikan Indonesia, 2025)
This study explores the relationship between independent learning and academic performance among sixth-grade students in the Gugus SD Karangmojo 2 cluster. The background of the problem lies in the increasing demand for self-directed learning skills in modern education, driven by technological advancements and the need for students to adapt to rapidly changing environments. Using a quantitative research design, data were collected from 30 students across five elementary schools through a questionnaire assessing independent learning with 15 Likert-scale items. Academic performance was evaluated based on students’ recent test scores in key subjects, including mathematics, science, and social. The analysis, utilizing univariate and bivariate statistical methods, revealed a significant positive correlation between independent learning and academic performance. This research finds that students who exhibited higher levels of self-directed learning tended to achieve better academic outcomes, highlighting the crucial role of independent learning in educational success. The contribution of this research lies in its empirical evidence supporting the integration of self-regulation and autonomy-promoting strategies in elementary education, which can enhance academic achievement and foster lifelong learning skills. These findings suggest that fostering self-regulation and autonomy in students can enhance their academic achievement.